1994
DOI: 10.1073/pnas.91.10.4446
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of human basic A1, a distinct 59-kDa dystrophin-associated protein encoded on chromosome 8q23-24.

Abstract: Duchenne and Becker muscular dystrophies are caused by defects of dystrophin, which forms a part of the membrane cytoskeleton of sp d cells such as muscle. It has been previously shown that the dystrophin-asocited protein Al (59-kDa DAP) is actually a heterogeneous group of phosphorylated proteins consisting of an acidic (a-Al) and a distinct basic ((-Al) component. Partial peptide sequence of the Al complex purified from rabbit muscle permitted the design of oligonucleotide probes that were used to isolate a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
92
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 26 publications
6
92
1
Order By: Relevance
“…The sequences of these clones showed that they code for truncated forms of already known proteins. The product of clone 15 is highly homologous to the PSD-95 protein (Brenman et al, 1996) and that of clone 43 to the b1-syntrophin (Ahn et al, 1994). Clone 15 encodes a protein including only the PDZ1 and PDZ2 domains, but lacking the PDZ3, SH3 and guanylate kinase domains present in the carboxy-terminal part of PSD-95.…”
Section: Binding Of Tax To Pdz Proteinsmentioning
confidence: 99%
“…The sequences of these clones showed that they code for truncated forms of already known proteins. The product of clone 15 is highly homologous to the PSD-95 protein (Brenman et al, 1996) and that of clone 43 to the b1-syntrophin (Ahn et al, 1994). Clone 15 encodes a protein including only the PDZ1 and PDZ2 domains, but lacking the PDZ3, SH3 and guanylate kinase domains present in the carboxy-terminal part of PSD-95.…”
Section: Binding Of Tax To Pdz Proteinsmentioning
confidence: 99%
“…A third subcomplex of the dystrophin-associated protein complex involves ␣-dystrobrevin (10)(11)(12) and the syntrophins (␣1, ␤1, and ␤2) (13)(14)(15). These intracellular proteins directly bind to dystrophin (16,17).…”
mentioning
confidence: 99%
“…Using partial peptide sequences generated from proteolytic digestion of the rabbit 50-kDa DAP, Roberds et al (13) identified a cDNA encoding the rabbit 50-kDa DAP and termed it adhalin. Isoelectric focusing analysis of the smaller components of the glycoprotein complex has suggested that the 35-kDa DAP may be heterogeneous (8).Dystroglycan and the syntrophins are expressed in tissues that lack the full-length dystrophin (10)(11)(12). This has raised speculation that in vivo, dystroglycan and the syntrophins may interact with proteins other than dystrophin.…”
mentioning
confidence: 99%
“…Dystroglycan and the syntrophins are expressed in tissues that lack the full-length dystrophin (10)(11)(12). This has raised speculation that in vivo, dystroglycan and the syntrophins may interact with proteins other than dystrophin.…”
mentioning
confidence: 99%
See 1 more Smart Citation